Pre-Service Teachers’ Integration into Teachers’ Community during Teaching Practicum - Afrianto Afrianto (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2017)
Abstract: Teaching practicum is a strategic place where pre-service teachers transformthemselves from being pre-service teachers (PSTs) to become novice teachers. Datafrom a case study on how a group of PSTs experience integrate into teachers’community during teaching practicum in Indonesian context shows that their journeyis not linear; it encompasses a complex process, enriched by tension and conflict beforesome of them hold a sense of belonging to teachers community in their placementschools. Their ample engagement and participation with members of schoolcommunity during teaching practicum program have effectively played as a significantfactor behind their integration and identity transition.Keywords: teaching practicum, pre-service teachers, identity construction, teachers community, integration, identity in transition